Solar collectors based on luminescent 2, 5-diarylimidazoles. (October 2018) - Marianetti, Giulia; Lessi, Marco; Barone, Vincenzo; Bellina, Fabio; Pucci, Andrea; Minei, Pierpaolo
Abstract: We report on the synthesis of new fluorescent symmetrical 2, 5-diaryl-1-methylimidazoles obtained in good yields by using direct C-H arylation synthetic strategies. Spectroscopic investigations in THF solution evidenced that the 2, 5-diarylimidazole bearing the strong electron-withdrawing cyanoacrylate groups achieved the best trade-off between fluorescence maximum (518 nm), Stokes shift (115 nm) and a quantum yield of 25%. Highly homogeneous dispersions of the selected fluorophore in poly(methyl methacrylate) (PMMA) thin films (25 ± 5 μm of thickness) perfectly maintained the optical features in solution, thus providing a brilliant green emission and a markedly enhanced quantum yield of 55%. Photocurrent measurements of the PMMA collectors supported the use of 2, 5-diaryl-1-methylimidazoles as accessible alternatives to perylene backbones for the development of LSC with optical efficiencies close to 7%. Graphical abstract: Highlights: 2, 5-Diarylimidazoles are bright fluorescent in solution and in PMMA thin films. Wide Stokes shifts and good QY characterize push-pull 2, 5-diarylimidazoles. A direct arylation protocol opens the way to selected 2, 5-diarylimidazoles. Fluorescent 2, 5-diarylimidazoles are thermally stable up to 220 °C. LSCs based on push-pull azoles may be a choice cheaper than perylene-based devices.